2014
DOI: 10.1088/1741-2560/11/1/016004
|View full text |Cite
|
Sign up to set email alerts
|

Intention estimation in brain–machine interfaces

Abstract: Objective The objective of this work was to quantitatively investigate the mechanisms underlying the performance gains of the recently reported ‘recalibrated feedback intention-trained Kalman Filter’ (ReFIT-KF). Approach This was accomplished by designing variants of the ReFIT-KF algorithm and evaluating training and online data to understand the neural basis of this improvement. We focused on assessing the contribution of two training set innovations of the ReFIT-KF algorithm: intention estimation and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 65 publications
3
124
1
Order By: Relevance
“…Importantly, however, we found that our LMP-driven BMI performance was not as good as spike-driven performance using the state-of-the-art FIT-KF algorithm [49]. Thus, while our results demonstrate that LMP is a viable alternative control signal to spikes, we do not suggest employing LFP-only decoding if good spikes are available.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Importantly, however, we found that our LMP-driven BMI performance was not as good as spike-driven performance using the state-of-the-art FIT-KF algorithm [49]. Thus, while our results demonstrate that LMP is a viable alternative control signal to spikes, we do not suggest employing LFP-only decoding if good spikes are available.…”
Section: Discussionmentioning
confidence: 61%
“…We felt that it would be most impactful to try to improve performance and robustness above that of a current state-of-the-art spikes decoder. We therefore used as our baseline the FIT-KF algorithm [49] and then extended it to decode both spikes and LMP. When both spikes and LMP were decoded from all available electrodes, hybrid decoding enabled a modest improvement in closed-loop performance in monkey R, but was marginally worse than spikes-only decoding in monkey J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This task has previously been described in prior work (e.g., [5], [15], [16], [36], [37]). The virtual cursor and targets were presented in a 3D environment (MSMS, MDDF, USC, Los Angeles, CA) [38].…”
Section: A Experimental Setup and Data Acquisitionmentioning
confidence: 99%
“…Presumably the more accurate the decoder, the simpler, and more intuitive will be the user adaptation. Further performance improvements could be achieved through user adaptation, combined with continued decoder adaptation and retraining [2, 9, 12, 15]. …”
Section: Discussionmentioning
confidence: 99%